Integration model for health services in the colombian social security system Modelo de integración de servicios de salud del sistema - Aparicio Pico, Lilia Edith; Arco Ríos, Pedro; López Sevillano, Alexandra (Tecnura, 2014)
Thisarticle proposes anIntegration Modelfor Health Serviceswhose extent ofcomplexity ofcareare included inthe General System ofSocialSecurity in Health(SGSS) aimed at setting up a basic toolto enhance the effectiveand decisiveresponseof the Colombian HealthcareSystem inthe use and managementof resources.Themodelallowscarrying out an intrinsicassessment ofthe systemadministration, as well as of the resources and actors tobe applicable to otherintegration systems and managementof hospital resourcesat the nationaland international consensus. The analysis ofcomplex systemsis takenas fundamental issues to abstractthe basic structure ofinteractionsand assessment of possibleemerging situationsin the Management ofHealth System.